Pengaruh Daya Tarik Pembawa Acara dan Program Televisi Terhadap Minat Menonton “Brownis” Trans TV - Miranda Amelia; Abellia Natasya; Surianto Surianto (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2026)
Communication is an important aspect of human life as it enables individuals to interact, fulfill needs, and build social relationships. The development of communication has led to the concept of mass communication, one of which is through television as a medium of entertainment and information. Competition among television programs encourages broadcasters to present attractive content through host attractiveness and program quality. This study aims to determine the influence of host attractiveness and television programs on viewing interest in the “Brownis” program on Trans TV. This study uses a quantitative method with a survey approach. Data were collected through questionnaires distributed to respondents who are familiar with the “Brownis” program. The results indicate that host attractiveness and television programs influence viewing interest. Attractive hosts and high-quality, entertaining programs can increase audience interest in watching the program. The conclusion is host attractiveness and program quality are important factors influencing viewing interest. The better these aspects, the higher the audience’s interest in watching the “Brownis” program.